Synthesis and Properties of New Side-Chain Liquid Crystalline Polymers by Metathesis Cyclopolymerization - Choi, S.-J.; Kim, S.-H.; Ahn, W.; Ahn, W.; Choi, S.-K. (1994)
New thermotropic side-chain liquid crystalline polymers containing a poly(dipropargylamine) backbone were prepared by metathesis polymerization with transition metal catalysts. It was found that the MoCl5-EtAlCl2 catalyst system was very effective for the cyclopolymerization of the presently investigated monomers. The resulting polymers exhibited good solubility in common organic solvents such as tetrahydrofuran (THF), chloroform, etc. and could be cast on glass plates to give dark-brown films. The structure of the polymers was confirmed by IR, UV-visible, and 1H and 13C NMR spectra. The number average molecular weight (Mn) values of the polymers were in the range 6.49 × 103-1.8 × 104 relative to polystyrene standards by GPC. The thermal properties of the monomers and the polymers synthesized were analyzed by differential scanning calorimetry (DSC), cross-polarized optical microscopy, and X-ray diffraction analysis. Both monomers and polymers displayed enantiotropic liquid crystallinity. The room-temperature conductivities of the undoped and I2-doped polymers were found to be about 10-11 and 10-3 S/cm, respectively. ？ 1994, American Chemical Society. All rights reserved.